Follow-up Status of Patients Referring to Secondary and Tertiary Hospitals in Family Health Centers - Gökçeoğlu, Sonay; Ceylan, Mehmet Reşat; Beyaz, Emine (Kare Publishing, 2024)
Objectives: This study aimed to evaluate the frequency of patients' preference for other health care services instead of receiving health care services from Family Health Center (FHC) and the factors affecting this preference. Methods: The cross-sectional study involving 1217 patients was conducted between 12 and 22, December 2023. Among the patients who applied to the outpatient clinic, all patients who agreed to participate in the study were included in the study without skipping a line. Thus, the sample group was randomly selected. Data were collected using a structured information form. Face-to-face interviews were conducted with the patients in the study. Results: The study included 1217 patients who were admitted to the hospital for outpatient treatment, and 729 (59.9%) of the patients were treated in hospitals despite being eligible for diagnosis and treatment at the FHC. When the factors determining the tendency to seek care in FHC were evaluated, being 18 years of age or older 2.133 times (CI: 1.518–2.997; p<0.001), being literate or more educated 2.410 times (CI: 1.713–3.391; p<0.001), having income equal to or more than expenses 2.418 times (CI: 1.712–3.415; p<0.001), having a large family type 418 times (CI: 1. 712–3.415; p<0.001), having a large family type 1.954 times (CI: 1.309–2.917; p=0.001), being satisfied with the FHC 1.515 times (CI: 1.058–2.170; p=0.023), having a complaint duration of 8–90 days 2.368 times (CI: 1.465–3.828; p<0.001) have an effect. Conclusion: In this study, 59.9% of hospital admissions were found to be unnecessary admissions, suggesting that primary health care services are not used effectively. © 2024 Kare Publishing. All rights reserved.
Keywords: Health care system; outpatient health services; primary healthcare; public hospitals; referral